Identifying Fake News: A Lesson from Library Science Students - Nora Saiva Jannana; Thoriq Tri Prabowo; Ratna Istriyani Istriyani (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2021)
This study aims to determine the level of the Library Science student’s awareness at UIN Sunan Kalijaga Yogyakarta to prevent spreading fake news from the internet. This was carried out by identifying fake news with indicators by the International Federation of Library Associations (IFLA). This research is a quantitative descriptive study. The data were obtained through questionnaires, interviews, and non-participative observation. The grand mean was used to conclude the data from the collected questionnaires. The results showed that the students' awareness of fake news was included in the high category, with a score of 3.77 from grades 1 to 5. Students of Library Science at UIN Sunan Kalijaga had the willingness and ability to recognize hoaxes on the internet, including 1) willingness to ask experts, 2) ability to understand news contexts, 3) willingness to check the sources of the news, 4) ability to read between the lines, 5) willingness to avoid prejudice (being neutral), 6) willingness to check the news production time (date), 7 ) willingness to examine news writers, and 8) willingness to examine supporting sources for news production. Students should implement critical thinking as the main skill for identifying fake news. Information literacy education can be used as a way to get their critical thinking skills.